The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.joms.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Anesthesia Is Associated With Shortened Length of Hospital Stay Following Orthognathic Surgery

Abstract: Induced hypotensive anesthesia represents a potential factor that minimizes postoperative LOS for patients undergoing routine maxillary orthognathic surgery alone or in combination with mandibular procedures. Hypotensive anesthesia does not appear to be effective in minimizing the duration of surgery within this same patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…We observed that the cardiac index and ScVO 2 decreased significantly; however, these values were within normal limits and arterial blood gas results remained normal while performing CH. These findings confirmed the safety of CH from 50 to 65 mmHg in young healthy patients that was reported previously [3][4][5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that the cardiac index and ScVO 2 decreased significantly; however, these values were within normal limits and arterial blood gas results remained normal while performing CH. These findings confirmed the safety of CH from 50 to 65 mmHg in young healthy patients that was reported previously [3][4][5].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it provides a better surgical environment and reduces the time involved in hemostasis, thereby shortening the operative time [2]. The current data retrieved from several articles indicate that mean arterial blood pressure (MBP) within the range of 50 to 65 mmHg is safe for young and healthy patients [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data gathered on surgery field visibility is inconsistent, assuming that subjectivity of the evaluation and different pharmacological agents' interactions may have affected the results [18,19,21,25]. Additionally, the reflection of the bleeding control on shorter surgery duration was not observed [26]. Moreover, pain is frequently observed in orthognathic surgery, therefore, adequate pain control is crucial [27].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the use of deliberate hypotension can shorten the operative time, reduce the risk of tissue edema caused by ligation or electrocautery, and improve myocardial performance by reducing cardiac preload and afterload [4, 6]. A recent retrospective cohort study indicates that deliberate hypotension has a potential ability to minimize length of hospital stay for patients undergoing orthognathic surgery [7]. In 2007, moreover, a meta-analysis provides evidence to support for the use of deliberate hypotension in orthopedic surgery [8].…”
Section: Introductionmentioning
confidence: 99%